Study the effect of stable magnetic field on the inhibition activity of Saccharomyces boulardii against pathogenic bacteria isolated from urinary tract infection (Baghdad Science Journal, 2017)
An increasing trend to use probiotic and study their effects on the pathogens has been conductor where they are defined as live micro-organisms that give a health benefit to the host when ingested in sufficient quantities, including the yeast Saccharomyces boulardii In addition research show that a magnetic field (MF) has a biological effect. This study aims to investigate the effects of magnetic field on the inhibitory action of Saccharomyces boulardii against bacteria isolated from urinary tract infection, Study the sensitivity of bacterial isolates to antibiotics after diagnosis by microscopic, Cultural and biochemical examinations as well as Api20 E examinations were used gram negative bacteria , Most isolates were resistant to antibiotics elected, using Well diffusion method to investigate the inhibitory action of suspension and supernatant of the yeast with and without magnetic field in four different intensities (200-300-400-500) milli Tesla. The results show that inhibitory efficacy of each was higher wish increasing the magnetic field strength and differed in their impact depending on the type of bacteria and the isolate of K.pneumoniea was the most sensitive in all experiments, and suspension was more effective.